The Chronology of Economic Instabilities of the EAEU Countries - Hovsepyan, Meri («Տնտեսագետ» հրատ․)
As economic history has shown, economic instabilities that originate in one country can be transmitted through various mechanisms and affect not only individual countries but also integration associations and their integration processes and economic developments. Moreover, if in the initial period this impact is noticeable only for the economic prospects of the trading partners, later it gains a global character and affects other partner countries after a certain time lag. Considering recent economic developments, the same pattern is applied in the case of the Eurasian Economic Union (EAEU). Being former members of the USSR, EAEU member countries have faced systemic crises since their independence until these days. This article summarizes the chronology of the economic crises that took place in the EAEU member states, elaborates, clarifies, and classifies their characteristics. Based on this, the author aims to explore the differences and similarities of the economic development cycles of the EAEU countries.
Keywords: International economics